Unravelling Salt Structural Evolution: Case Study from West Africa - Nila Murti (Berita Sedimentologi, 2003)
The offshore area of Guinea Bissau is part of the Mauritania-Senegal Basin that forms a part of Mesozoic-Cenozoic basin in the Central Atlantic passive margin of West Africa. Its geological history reflects the evolution of the Atlantic Ocean. The area is also located in one of the salt basins in West Africa, with a syn-rift salt sequence or Triassic-Early Jurassic age. The sequence formed various salt structures, which provide potential hydrocarbon trapping mechanisms. To reveal the distribution and evolution of the salt structures in the Offshore Guinea Bissau will lead to the better understanding of interaction between the sediments and the structures. The study will also give explanation for reservoir distribution, the timing of trap formation and the shape of salt structures, hence helping to better locate the prospects in hydrocarbon exploration activity.